Strategi Penentuan Harga Jasa Pendidikan - Aminah, Neneng; Auliya, Haya Yumna Ilmin; Zohriah, Anis; Muin, Abdul (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2025)
Pricing of educational services is a strategic aspect in educational institution management that influences accessibility and operational sustainability. This study aims to analyze various educational service pricing strategies through a literature review to identify the optimal pricing model for educational institutions. The research method uses a literature study approach by analyzing journal articles, books, and scientific publications related to pricing strategies in the education sector from various academic databases. The analysis was conducted descriptively and analytically to identify patterns, trends, and best practices in educational pricing. The results of the study indicate that there are four main approaches to determining educational service prices: cost-based pricing, value-based pricing, competitive pricing, and penetration pricing. Factors influencing pricing strategies include operational costs, service quality, institutional positioning, market segmentation, and the economic conditions of the target market. The literature review revealed that value-based pricing combined with an analysis of the community's economic capacity provides optimal results in balancing profitability and accessibility. The study's conclusions indicate that determining educational service prices requires a multifactorial approach that considers economic, social, and service quality aspects to achieve the sustainability of educational institutions.